The Role of Teacher Supervision in Learning Quality - Maulana Eka Pratikta; Widya Rahmadatul Setiani; Selvia Lovita Sari; Maya Mardani; Undang Rosidin; Chika Rahayu (Foundation of Jannatun Naim Lampung, 2025)
Educational supervision in schools plays an important role in maintaining and improving the overall quality of education. The quality of education is determined by various factors, one of which is the role of teachers. This study aims to explore the role of teacher supervision in learning quality. This research uses a descriptive qualitative method, so it is necessary to conduct observations and interviews in one of the public junior high schools in Central Lampung District. The result obtained from this research is that the role of teacher supervision is very important in improving the quality of learning in schools. Supervision that is carried out in a planned and data-based manner has a positive impact on the capacity development of teachers and principals. Various challenges faced in implementing supervision, such as managerial busyness, lack of preparation from teachers, and limited facilities, can be overcome with improved coordination, more careful planning, and the use of technology to support the supervision process. This teacher supervision is seen in the improvement of learning quality, more effective education management, and better achievement of educational goals. Thus, teacher supervision plays an essential role in creating a quality and sustainable learning environment.